Use of the Kinect sensor measured three-dimensional reachable workspace to assess the upper extremity function in older adults. (October 2022) - Koh, Eun Sil; Kurillo, Gregorij; Han, Jay J.; Lim, Jae-Young
Abstract: Background: We explored the utility of Kinect sensor-based upper extremity reachable workspace measure in healthy adults aged over 65 years. Methods: Forty-three healthy older subjects (19 men and 24 women) aged over 65 years and 22 healthy young subjects (11 men and 11 women) were included. All participants were ambulatory and perform the activities of daily living independently. Three-dimensional reachable workspace data were acquired for both arms using the Kinect sensor. We evaluated hand grip strength, manual muscle shoulder strength, and the active shoulder ranges of motion of the dominant and non-dominant sides. We assessed upper limb function using the Disabilities of Arm, Shoulder, and Hand (DASH) instrument and the health-related quality of life employing the descriptive EQ-5D-5L system. Findings: The quadrant 3 relative surface area in older adults was significantly smaller than that of young adults (both dominant and non-dominant sides), while the total and quadrants 1, 2, and 4 relative surface areas did not differ between older and young adults. However, the quadrant 3 relative surface area did not correlate with the DASH or EQ5D scores. The total and quadrant 1, 2, and 4 relative surface areas of the dominant side significantly correlated with the DASH score. The quadrant 4 relative surface area of the dominant side significantly correlated with the EQ5D score. Interpretation: Kinect sensor-based, three-dimensional, reachable workspace analysis may be useful to evaluate upper limb function in older adults. Highlights: The total relative surface area of the dominant side correlated with upper limb function. Quadrants 1, 2, and 4 relative surface area of the dominant side correlated with upper limb function. Quadrant 4 relative surface area of the dominant side correlated with the quality of life. Kinect-based reachable workspace may be useful to evaluate upper limb function in older adults.